Da Assembleia à Câmara: Michele Collins entre a igreja e o Estado laico. - Brandão, Rafael Ribeiro (2022)
The purpose of this dissertation is to bring concepts and interpretations about the secular State, as well as seeking to understand the interaction of politics and religion in Brazilian society. The study also alludes to the importance of knowing the meaning of republicanism in the relationship between faith and the public sphere and, from the general context, it seeks to analyze and understand the practices and agendas defended by the Evangelical Parliamentary Front, popularly known as the Evangelical Bench. It will also examine how conflicts of ideas arise within a society that does not adhere to the doctrinal basis that religious politicians try to instill in government programs. Topics including LGBTQIA+ groups, the issue of abortion, religious freedom, the role of women in society and the use of marijuana for medicinal purposes are the main focus of these conflicts, as demonstrated in the arguments, that religious agents sometimes use politics as an extension of their churches and enter into the antagonism of those who oppose the agenda of the Evangelical Bench. The dissertation emphasizes that the creation of the 1988 Constitution gave more political strength to religious groups, which are increasingly expanding at the federal, state and municipal levels. And in this work, as a specificity, a study was carried out with some controversies of these guidelines that were connected with the Recife city councilor, the missionary Michele Collins. The relationship between secularism, the public sphere, republicanism and religious opinions of this councilor is the analysis that will be carried out here. In which it will be discussed that the defense of the existence of a Democratic State of Law must respect ideological plurality. The research involved analyzing the theme of secularism and the religious influence in the State. Radiographing theorists who approach this analysis of faith influencing the State and how it influences the behavior of faithful voters. The present work was carried out through journalistic reports and bibliographic review with books, articles and master's dissertations. And it results in the understanding that the State must be non-confessional and respect ideological plurality.